The Influence Of Gymnastics Diabetic Foot To Decrease Blood Sugar Levels In Patients With Type 2 Diabetes Mellitus - Untung Halajur; Riki (Publisher Cv. Inara, 2021)
Diabetes mellitus is a group of symptoms that arise in a person caused by an increase in blood glucose levels due to reduced insulin secretion are progressive background by the retention of insulin. Gymnastics diabetic foot is needed in the management of diabetes mellitus, regular physical exercise can lower blood sugar levels. To examine the effect of diabetic foot gymnastics to decrease blood sugar levels in patients with Diabetes Mellitus as type 2 Clubs Prolanis Sanang Barigas BPJS Palangkaraya. Method This study is a quantitative research study design Preexperimental Design, the design of the study one-group pre-post-test design. The number of respondents 30 people. Retrieving data using a questionnaire and analyzed using SPSS. Statistical test using the Wilcoxon Signed RankTest. Results Statistical test results obtained Wilcoxon Signed Rank Test average value (mean) pretest / before gymnastics at 6:06 and posttest leg / foot after gymnastics at 18.93 while the value of the probability p value or sig. (2-tailed) 0.00 <0.05 (0.00 less than 0.05) so that Ho refused and Ha accepted which means there is a significant difference between random blood sugar levels before and after exercisefeet. Conclusion regular physical exercise and the effect on blood sugar levels drop as in patients with type 2 diabetes mellitus in prolanis club Sanang barigas BPJS Palangkaraya. so that exercisers diabetic foot is needed in the management of diabetesmellitus.